Identification of Driving Factors of Sustainable Innovation in MSMEs in the Food, Beverage, and Service Sectors in West Java - Putri, Mediany Kriseka; Anjangsara, Faisal Ahsan (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to explore sustainable innovation within MSMEs in West Java, focusing on understanding, and driving factors. Utilizing a qualitative approach, we conducted interviews with 11 MSMEs from the food, beverage, and service sectors. Our findings indicate varying levels of awareness of sustainable innovation, with primary external drivers being market competition and consumer demand, while the internal driver is MSMEs decision. The study highlights the need for targeted support to enhance SME innovation capabilities, and emphasizing the role of continuous learning. These insights contribute to the broader knowledge of sustainable practices in MSMEs.